ALIH FUNGSI LAHAN PERTANIAN DI KABUPATEN BOLAANG MONGONDOW TIMUR - Vecky ., Manoppo; Benu Olfie L. S.; Agnes E. Loho (Sam Ratulangi University, 2018)
This study aims to know and identify the cause of land conversion in East Bolaang Mongondow Regency. This research will be conducted for 3 months. The data in this research is secondary data. Secondary data is data obtained by related institutions such as BPS (Central Bureau of Statistics), sub-district office and village office. The method used is descriptive method. The results showed that the cause of the occurrence of agricultural land conversion in East Bolaang Mongondow Regency due to the increasing number of population and economic factors that encourage people willing to sell their plantation land to be a place of business and government policies for road construction. From the three factors of land conversion, most the prominent is the increasing of population.*jnkd*.